2015
DOI: 10.1124/jpet.115.224428
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dopamine Type 1 Receptors and Dopamine- and cAMP-Regulated Phosphoprotein Mr 32 kDa in Δ9-Tetrahydrocannabinol–Mediated Induction of ΔFosB in the Mouse Forebrain

Abstract: D 9 -Tetrahydrocannabinol (THC), the main psychoactive component of marijuana, produces motor and motivational effects via interactions with the dopaminergic system in the caudateputamen and nucleus accumbens. However, the molecular events that underlie these interactions after THC treatment are not well understood. Our study shows that pretreatment with dopamine D 1 receptor (D 1 R) antagonists before repeated administration of THC attenuated induction of D FBJ murine osteosarcoma viral oncogene homolog B (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…First, a history of repeated THC treatment enhanced acute THC-mediated increases in ΔFosB mRNA in PFC and NAc. We previously reported that repeated THC treatment induced ΔFosB protein in PFC, NAc, CPu, and amygdala 20 , 23 as replicated here, and prior studies showed that repeated treatment with psychostimulants 24 or morphine 25 induced ΔFosB in these same regions. Second, induction of ΔFosB by repeated THC treatment was associated with increased expression of Cdk5 and p35 only in PFC.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…First, a history of repeated THC treatment enhanced acute THC-mediated increases in ΔFosB mRNA in PFC and NAc. We previously reported that repeated THC treatment induced ΔFosB protein in PFC, NAc, CPu, and amygdala 20 , 23 as replicated here, and prior studies showed that repeated treatment with psychostimulants 24 or morphine 25 induced ΔFosB in these same regions. Second, induction of ΔFosB by repeated THC treatment was associated with increased expression of Cdk5 and p35 only in PFC.…”
Section: Discussionsupporting
confidence: 86%
“… 15 , 30 The reason that Cdk5 is induced in different regions by THC versus cocaine is not known. ΔFosB induction by both THC and psychostimulants requires D 1 R activation, 20 , 24 suggesting a common upstream site of action. Both drug classes induce ΔFosB in D 1 R/dynorphin-expressing medium spiny neurons (MSNs) in the NAc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each brain region was dissected as we have described (Lazenka et al, 2014; Lazenka et al, 2015), flash frozen and stored at −80 °C. On the day of each assay, samples were thawed, homogenized in ice-cold membrane buffer (50 mM Tris–HCl, pH 7.4, 3 mM MgCl 2 , 1 mM EGTA and 100 mM NaCl) and centrifuged at 48,000 × g at 4 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%